Intravenous immunoglobulin significantly reduces exposure of concomitantly administered anti‐C5 monoclonal antibody tesidolumab. Issue 9 (13th May 2020) - Jordan, Stanley C.; Kucher, Klaus; Bagger, Morten; Hockey, Hans‐Ulrich; Wagner, Kristina; Ammerman, Noriko; Vo, Ashley
Abstract : Awareness of drug‐drug interactions is critical in organ transplant recipient management. However, biologic agents interfering with monoclonal antibodies is not widely considered. We report the effect of high‐dose intravenous immunoglobulin (IVIg) on safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of the human anti‐C5 monoclonal antibody tesidolumab (LFG316) in end‐stage renal disease patients awaiting kidney transplant. In this single‐center, phase 1, open‐label, parallel‐group study, 8 patients were assigned to receive either single‐dose tesidolumab + IVIg or tesidolumab alone, with 56‐day follow‐up. Within‐group PK parameters were consistent. Mean tesidolumab exposure decreased 34%, clearance increased 63%, and half‐life decreased 41% comparing tesidolumab + IVIg to tesidolumab alone. IVIg influence on tesidolumab elimination was most evident in the first 3 weeks. Complete suppression of both total and alternative complement activities was maintained for 4 weeks in the tesidolumab alone group and for 2 weeks in the tesidolumab + IVIg group. Tesidolumab was well tolerated. IVIg infused before tesidolumab affected tesidolumab PK and PD, resulting in a shortened period of full complement activity inhibition. These findings suggest a clinically relevant impact of IVIg on monoclonal antibody clearance and indirectly hint at an IVIg mechanism of action in treating autoimmune diseases and allosensitization by accelerating pathogenic IgG antibody degradation. Trial registration number: NCT02878616. Abstract : This article shows that concurrent administration of high dose intravenous immunoglobulin causes a therapeutically relevant reduction in the complement inhibition efficacy of anti‐C5 monoclonal antibody tesidolumab.